An Overview of the Anatomical Distribution of Tetrodotoxin in Animals - Daria I. Melnikova; Timur Yu. Magarlamov (Toxins, 2022)
Tetrodotoxin (TTX), a potent paralytic sodium channel blocker, is an intriguing marine toxin. Widely distributed in nature, TTX has attracted attention in various scientific fields, from biomedical studies to environmental safety concerns. Despite a long history of studies, many issues concerning the biosynthesis, origin, and spread of TTX in animals and ecosystems remain. This review aims to summarize the current knowledge on TTX circulation inside TTX-bearing animal bodies. We focus on the advances in TTX detection at the cellular and subcellular levels, providing an expanded picture of intra-organismal TTX migration mechanisms. We believe that this review will help address the gaps in the understanding of the biological function of TTX and facilitate the development of further studies involving TTX-bearing animals.